Neuroscience of autism - Kana, Rajesh K. (Academic Press, an imprint of Elsevier, 2022)
"The Neuroscience of Autism provides a comprehensive accounting of autism spectrum disorders by integrating scientific findings from behavioral, cognitive and neurobiological research. The book begins by defining autism, identifying characteristics and prevalence, exploring its history, and then moving on to the cognitive and social bases of behavioral symptoms, the brain bases of behavioral and cognitive symptoms, and finally, intervention practices. It examines theoretical models such as weak central coherence, enhanced perceptual functioning, and the extreme male brain hypothesis. Finally, the book addresses the increased attention on the brain connectivity model of autism, looking at the synchronization of brain activity across different brain areas, the causal influence of a brain region on another, and white matter cable connections in the brain."--Publisher's description.